THE PRESENT STATUS OF MARKET INSTITUTIONS AS A FACTOR IN UKRAINE’S NATIONAL SECURITY AND COMPETITIVENESS - Struk, Oleksandra; Hurnyak, Ihor (Torun International Studies, 2024)
Purpose: This study explores the impact of market institutions on Ukraine’s national security and competitiveness. Specifically, it presents the role of the stock market and banking sector in shaping economic stability and defense capabilities. Methodology/approach: Drawing on insights from institutional economics, this research employs a comparative analysis of market institutions in Ukraine and other Central and Eastern European (CEE) countries. The study is based on data from the stock market and banking sector to assess their performance and implications for national security. Additionally, the Axelrod tournament framework is applied to analyze strategic behavior within these institutions. This analysis incorporates the utilization of various Python packages to delve into the complexities of the situation. The market of arms manufacturers is selected as an illustration of missed opportunities. Optimization of portfolios was carried out based on the maximization of the Sharpe ratio. At the same time, indicators Sortino, Max Drawdown, Calmar were used for testing alternative approaches. Findings: The analysis reveals significant shortcomings in Ukraine’s market institutions, particularly in the stock market and banking sector. Weaknesses such as underrepresentation of defense companies and other sectors in the stock market and high levels of nonperforming loans in the banking sector pose serious challenges to national security. Comparative analysis of such countries like Poland and Czech Republic highlights the importance of robust institutional frameworks. Analysis of WIG Ukraine and WIG CEE supports this conclusion. Institutional weakness does not allow Ukraine to maintain a stable proactive position in interaction with other states. Originality/value: This study contributes to the scientific discourse on institutional economics and national security by providing a comprehensive analysis of market institutions in Ukraine. By identifying key weaknesses and comparing them with successful institutional models in other CEE countries, the research underscores the urgency of institutional reforms to safeguard Ukraine’s interests and enhance its competitiveness on the global stage.